ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS DITINJAU DARI KEMANDIRIAN BELAJAR PADA PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN E-MODUL - Istiqomah; Kartono; Endang Wahyuningrum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analize the effectiveness of the e-module assisted discovery learning model on critical thinking skills and to describe students' critical thinking skills in terms of learning independence. The research design used was a mixed method design with an exploratory sequential design. The subjects were fifth-grade elementary school students in Paninggaran, Pekalongan. Data collection was carried out through interviews, observations, questionnaires, and documentation to obtain comprehensive information. Based on the results of the research data analysis, it was concluded that learning with the e-module-assisted discovery learning model was proven effective, there was an increase in students' critical thinking skills and independence after participating in the e-module-assisted discovery learning, and there was a relationship between the level of critical thinking skills and student independence. In addition, students with high ability categories were able to demonstrate optimal performance in all critical thinking indicators because they had mature learning independence. Students in the medium category show developing abilities, but still require teacher guidance, students in the low category face significant obstacles in every aspect of critical thinking and low learning independence. Suggestions based on the results of this study are that teachers need to provide intensive guidance, directed feedback, and reflective thinking exercises consistently to students with medium and low critical thinking abilities, to help them develop critical thinking abilities and learning independence. Schools need to design habituation programs that encourage the growth of critical thinking abilities and student learning independence, through reflective activities, group discussions, and modeling critical thinking strategies.